Characterization of Patients with Helicobacter pylori-Negative Peptic Ulcers - Roberto Hernández Conde; Guillermo Noa Pedroso; Carlos Domínguez Álvarez; Isabel Mora Díaz; Marcos Félix Osorio Pagola; Yagén Pomares Pérez (Medisur)
Background: the rate of Helicobacter pylori-negative ulcers is increasing. Treatment with nonsteroidal anti-inflammatory drugs and other ulcerogenic drugs plays a significant role. Objective: to characterize patients with Helicobacter pylori-negative peptic ulcer. Methods: a case series study of patients attended by the Gastroenterology Service of the Hermanos Ameijeiras Hospital was conducted in the year 2009. Demographic, epidemiological, clinical, endoscopic and histological variables were studied. Mean and standard deviation were analyzed; logistic regression, t-Student and Chi-square tests were used. Results: A total of 269 gastric ulcers, 239 duodenal ulcers and 41 combined were diagnosed; 115 cases were Helicobacter pylori-negative and 434 were positive. Nonsteroidal anti-inflammatory drugs were associated with 33,9 % of H. pylori-negative patients and 22.8% of the positive patients. Ulcerative syndrome occurred in 47 % and 45% in both groups. All H. pylori-negative duodenal ulcers were located in the duodenal bulb as well as 96, 6 % of the positive. The antrum was the most common location for gastric ulcerations (92.3% negative; 90.5% positive). Multiple ulcers predominated in the duodenum while double ulcers prevailed in the stomach, all negative for H.pylori. Antral gastritis predominated (73. 0 % H. pilory- negative), the level of activity was higher in the positive cases (97. 0 %) and intestinal metaplasia was similar for both groups. Conclusions: in patients with H. pylori-negative peptic ulcer, non-steroidal anti-inflammatory drugs should be taken into consideration as one of the main factors associated with this entity.